Schools and the politics of religion and diversity in the Republic of Ireland : Separate but equal? - Fischer, Karin, 1972- (Book collections on Project MUSE., 2016)
This book focuses on the historical and current place of religion in the Irish education system from the perspective of children's rights and citizenship. It offers a critical analysis of the political, cultural and social forces that have shaped the system, looking at how the denominational model has been adapted to increased religious and cultural diversity in Irish society and showing that recent changes have failed to address persistent discrimination and the absence of respect for freedom of conscience. It relates current debates on the denominational system and the role of the State in education to competing narratives of national identity that reflect nationalist-communitarian or republican political outlooks. This book will be essential reading for students and researchers in the fields of education policy and Church/State relations in Ireland and will also engage non-academic audiences with an interest or involvement in Irish education.